(untitled) ("Temas Sociais" Journal, 2021)
This research aims to analyze the dynamics of Social Work in the gerontoinstitutional field, in the light of a reflection on the various expressions of EA and participation, in benefit of life projects for and in old age. The sample involved five social workers working in Residential Structures for the Elderly (ERPI) from five different ERPIs. Data were collected through a sociodemographic questionnaire and in-depth interviews (semi-structured) following an essentially qualitative approach (content analysis). The main results showed that designing life projects for and in old age in residential settings consistently proved to be supported, on the one hand, by institutionalized standards and guidelines and, on the other hand, although emerging at a shy pace, by holistic, comprehensive and multidimensional approaches. These results are promising in terms of how analytically and empirically life projects based on the new expressions of old age(s) are conceived and implemented in residential care facilities, focusing on interactive, integrative and multidimensional logics.